Analisis Kemampuan Berpikir Kritis Matematis Pada Materi Aljabar Siswa Kelas VII MA Al-Mutmainnah Desa Punti Kecamatan Soromandi Kabupaten Bima - Astiati, Siska Dwi; Ilham, Ilham (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Critical thinking is thinking deeply, according to facts. The purpose of the study was to describe the mathematical critical thinking skills of MTs Al-Mutmainah Punti students in solving Algebra problems. This type of research is descriptive. Qualitative research approach. The subjects of this study were 1 high-ability student, 1 medium-ability student and 1 low-ability student. The data collection technique used a written test instrument. The data analysis technique used a qualitative descriptive analysis technique. The results showed that high critical thinking students met the four indicators, namely Analyzing and focusing, students were able to describe and simplify questions as the first step of completion. Identifying assumptions students make the completion steps to determine the results of the algebraic addition correctly. Determine and answer students with high abilities to solve problems in detail and systematically until they find the right answer. Making conclusions students rewrite the final results of the questions clearly and precisely. Furthermore, moderately capable students only meet the three indicators, namely analyzing and focusing questions correctly, identifying assumptions correctly and determining and answering a problem. While the indicators conclude that moderately capable students cannot do it. Finally, low-ability students cannot fulfill these four indicators. The conclusion is that high critical thinking students can solve problems according to the four indicators, while moderate and low thinking students solve problems that do not match the four indicators